Occupational nursing and the risks in times of Covid-19 pandemic (Research, Society and Development, 2021)
Objective: Reflectar acerca da vulnerabilidade dos profissionais de enfermagem diante dos riscos por acidente de trabalho. Conteúdo: trata-se de uma análise teórico-reflexiva, fundamentada em referenciais teóricos sobre acidente no trabalho pensando nos contextos vivenciados por enfermeiros e outros profissionais contaminados durante o combate a pandemia da covid-19. Final considerations: Based on this study, it was observed that the imminent risks in the nursing work reflect in the individual and collective dimensions of the groups, professionals and patients, being a combination of elements and experiences that intersect due to the emergency caused by the disease caused by the new coronavirus. It stands out, several difficulties encountered by health professionals beyond those related to the covid-19 disease, namely, the risks of accidents increased due to the spread of the disease in full expansion in Brazil.